2014
DOI: 10.1590/0074-0276130312
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the tissue inflammatory response in human cutaneous and disseminated leishmaniasis

Abstract: Cutaneous leishmaniasis (CL) is the most frequent clinical form of tegumentary leishmaniasis and is characterised by a single or a few ulcerated skin lesions that may disseminate into multiple ulcers and papules, which characterise disseminated leishmaniasis (DL). In this study, cells were quantified using immunohistochemistry and haematoxylin and eosin staining (CD4+, CD68+, CD20+, plasma cells and neutrophils) and histopathology was used to determine the level of inflammation in biopsies from patients with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…Initial studies showed that DL patients have more negative leishmania skin delayed type hypersensitivity test (LST) and an impairment in lymphocyte proliferation and in the production of interferon‐γ and TNF in supernatants of mononuclear cells stimulated with soluble leishmania antigen (SLA) as compared to CL patients . However, more recently, we document that cell‐mediated immune response at the lesion site of DL patients is similar to what is observed in CL ulcers . We believe that there is no impairment in T‐cell response in DL patients and raised the hypothesis that the poor T‐cell response observed in cells from peripheral blood was due to the migration of the majority of to the antigen reactive cells to the great number of lesions observed in DL patients .…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Initial studies showed that DL patients have more negative leishmania skin delayed type hypersensitivity test (LST) and an impairment in lymphocyte proliferation and in the production of interferon‐γ and TNF in supernatants of mononuclear cells stimulated with soluble leishmania antigen (SLA) as compared to CL patients . However, more recently, we document that cell‐mediated immune response at the lesion site of DL patients is similar to what is observed in CL ulcers . We believe that there is no impairment in T‐cell response in DL patients and raised the hypothesis that the poor T‐cell response observed in cells from peripheral blood was due to the migration of the majority of to the antigen reactive cells to the great number of lesions observed in DL patients .…”
Section: Introductionmentioning
confidence: 81%
“…8 However, more recently, we document that cell-mediated immune response at the lesion site of DL patients is similar to what is observed in CL ulcers. 6,9 We believe that there is no impairment in T-cell response in DL patients and raised the hypothesis that the poor T-cell response observed in cells from peripheral blood was due to the migration of the majority of to the antigen reactive cells to the great number of lesions observed in DL patients. 6 Moreover, these data suggest that parasite, more than host factors, may be involved in the pathogenesis of DL.…”
Section: Introductionmentioning
confidence: 98%
“…Firstly, sand fly- or needle-delivered promastigotes are converted into amastigotes within one to two days, when neutrophils are prevalent in the lesions. Secondly, neutrophils are ready detected in chronic forms of cutaneous leishmaniasis in patients infected with L. amazonensis, L. mexicana , or L. braziliensis [23,24] [25] [9]. At present, there is limited information on how neutrophils interact with these amastigotes.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of macrophages by interferon (IFN)-γ + produced by CD4 + T cells contribute to control parasite growth,3,4 whereas CD8 + T cells have been associated with pathology 57. Histopathological studies in ulcers of L-CL patients show an increase in inflammatory response, with the participation of T cells, B cells, plasma cells, macrophages, and the development of a granuloma 811. Although an intense lymphocyte proliferation and production of IFN-γ and tumor necrosis factor is induced on Leishmania antigen stimulation of peripheral blood mononuclear cells from patients with L-CL,12 in the preulcerative phase of the disease, lymphocyte proliferation, and cytokine production is lower than in patients with L-CL 13.…”
Section: Introductionmentioning
confidence: 99%